FORMALIZATION OF RELATIONSHIPS BETWEEN SYSTEM-PROVIDER AND SYSTEM-USER BASED ON STRUCTURED DATA FOR CONSOLIDATED PROCESSING - TYMCHUK, VOLODYMYR; HRAZION, DENYS; PELESHCHAK, IVAN; POPOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The tasks of consolidated processing of signals, data and information are inevitable because of the development of forms and methods of armed struggle. In systems of systems with flexible architecture, the set of input data will always be different, which makes the task of consolidated information processing in each application case unique. The formalization of the stages of the consolidated processing is the first step to look for an effective information technology for additional aspects in the relevant system of the basic methods and technologies. Modern weapons include computer information systems in which heterogeneous structured and unstructured data are generated and/or stored. The structured datasets are analyzed in a hierarchical multi-positional surveillance system. The article emphasizes information redundancy in the system due to the presence of non-informative or low-informative datasets from the point of view of the functional purpose of the data system. Distinctive features in each of the formalized datasets in the multi-positional surveillance system are also characterized, in particular, data related to registration within the system and data related to an event outside the system are distinguished. Taking into consideration the capabilities of machine learning systems and other artificial intelligence technologies, a place for such data operations as cleaning, classification, augmentation, correlation analysis, etc. is shown and it is the basis for the development of data post-processing algorithms. The design of effective IT for additional implementation in a hierarchical multi-positional surveillance system for the purpose of processing structured data and improving the characteristic description of the situation due to the consolidation of information and data will allow us to increase the effectiveness of functional systems and weapons samples in general.